Surgical Ventricular Restoration for Ischemic Cardiomyopathy with Functional Mitral Regurgitation - Hirota, Masanori; Katahira, Shintaro; Hoshino, Joji; Fukada, Yasuhisa; Kondo, Taichi; Gyoten, Takayuki; Notomi, Yuichi; Isomura, Tadashi (IntechOpen, 2012)
None